Simple spectrophotometric method for determination of iodine value of vegetable oils - Thidarat Kruatian (2018)
A spectrophotometric method has been developed for the determination of iodine value of vegetable oils. The method is based on the reaction of Hanus solution with oils and subsequently treated with potassium iodide solution producing triiodide ions. The absorbance at 350 nm of triiodide ions was used for analytical purposes. The calibration graph was constructed by plotting the absorbance at 350 nm versus the molar concentration of Hanus solution. Under the optimal conditions a linear calibration graph ranged from 0.02 to 0.10 mol/L of Hanus solution with r2 of 0.999. The proposed method was feasible to determine a wide range of iodine value of vegetable oil samples. The method was applied to commercially available vegetable oils and the results obtained by the proposed method agreed well with those obtained by the reference method. The standard deviation of iodine value ranged from 0.7 to 2.1 (n=3). The analytical procedures were simple, required short analysis time, and used small amount of solvent and reagent.